Hospital Pharmacy Management System and Future Development Approaches in Bangladeshi Hospital - Saha, Tushar; Bhuiya, Robiul Hasan; Masum, Zia Uddin; Islam, Muhammad Rashedul; Chowdhury, Jakir Ahmed (Bangladesh Pharmaceutical Journal, 2018)
The aim of this present work is to find out a suitable and updated hospital pharmacy management system for Bangladesh. Hospital pharmacy is considered as the heart of any hospital because all the departments like surgery, cardiology, nephrology, medicine, pediatric etc. are linked up with pharmacy section. Although the pharmaceutical sector of Bangladesh is enriched so much and the product is up to the mark but the improper management system in hospital pharmacies make the patient’s burden high. So, development is required in hospital pharmacy to ensure the proper choice, preparation, store, compounding and dispense of medicine as well as medical devices along with counseling for patient’s safety and compliance. Bangladesh Pharmaceutical Journal 20(2): 180-187, 2017